Rare variants in nucleotide methylation genes and neurodevelopmental disorders - Parke, Adam (2019)
Nucleotide methylation has a function in genomic repair, and in the regulation of transcription and translation. DNA methylation processes have been previously associated with developmental delay, dementia and neuronal death phenotypes. RNA methylation, a field in its infancy, has been associated with cancer and neurological disorders. However, much of this research is still in its early stages. Using next-generation sequencing data to screen DNA and RNA methylation genes, this thesis aims to investigate nucleotide methylation and genetic risk for neurological and neuropsychiatric diseases.